Synthesis of carbon-11 and fluorine-18 labeled N-acetyl-1-aryl-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline derivatives as new potential PET AMPA receptor ligands - Gao, Mingzhang; Kong, Deyuan; Clearfield, Abraham; Zheng, Qi-Huang (Bioorganic & medicinal chemistry letters, 2006)
New carbon-11 and fluorine-18 labeled N-acetyl-1-aryl-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline derivatives were designed and synthesized as potential positron emission tomography AMPA (2-amino-3-(3-hydroxy-5-methylisoxazol-4-yl)propionic acid) receptor ligands to image brain diseases. The single crystal structure of the most potent compound N-acetyl-1-(4′-chlorophenyl)-6,7-dimethoxy-1,2,3,4-tetrahydroisoquinoline ( 5a) is first reported.